ANALISIS TINGKAT KEBUGARAN FISIK MAHASISWA PENDIDIKAN OLAHRAGA MELALUI LATIHAN WEIGHT TRAINING - Raden Isnanta (Program Studi PGSD Universitas Flores, 2024)
Students of the Sports Education Study Program experience problems of fatigue, lack of concentration, and inmotivation during theoretical lectures and practical activities that require endurance and flexibility. These observations indicate that a lack of physical fitness may affect academic performance and active participation in physical activity. The study aims to analyze the physical fitness of students through Weight training to improve their strength, endurance, and flexibility. This study used quantitative descriptive method by applying Weight training Exercise as an intervention. Analysis of the level of physical fitness showed that the strength aspect reached the high category by 60%, the endurance aspect reached the high category by 50%, and the flexibility aspect reached the high category by 40% of the total number of students. Weight training with exercise intensity, duration, regular diet, and adequate rest can effectively increase the strength, endurance, and flexibility of Sports Education Study Program students. This is very relevant to the purpose of sports education that wants to improve the physical abilities of students, both for the benefit of sports and health in general.